(untitled) (International Journal of Engineering Materials and Manufacture, 2025)
Oil extracted from Mormyrus rume is highly valued for its nutritional benefits, highlighting the need for a simple and efficient processing device for fish oil extraction. This study focused on developing a contamination-free fish oil extruder. The machine was designed based on the principle of pressure differentials, where the pressure applied to the incoming fish pulp is compared to that exerted on the discharged material. Preheated fish are poured through the machine hopper and were compressed through a tapered screw conveyor with a shaft that narrows towards the discharge end and both the pressliqour and the cake are collected via the discharge outlets The maximum fish oil yield of 28.5 % was obtained from Mormyrus rume at a screw diameter of 42.5 mm and a pressing time of 15 minutes. The machine’s throughput capacity was recorded at 0.75 kg/h, while the oil expression rate was 0.2 kg/h at a fish-to-water ratio of 2:0.5. The highest oil expression efficiency of 80.0% was achieved at a heating time of 10 minutes, a screw diameter of 42.5 mm with a constant screw rotation speed of 55 rpm. The machine is expected to be applicable for extracting oil from other fish species and oil-bearing materials with similar physical properties. This innovation presents a reliable and efficient method for the mechanical expression of high-quality fish oil.